Financial accounting and reporting : a global perspective / Hervé Stolowy; Yuan Ding, (Accountant) - Stolowy, Hervé
Now in its sixth edition, Financial Accounting and Reporting: A Global Perspective is used worldwide by business and management students seeking an essential introduction to the field. Guidance through the complexities of financial accounting is offered from an international and ‘user’ perspective, based on the latest IFRS Standards. Its comprehensive coverage incorporates original case studies, decision-making orientation and real-life company financial statements from across the globe, maximizing topicality and relevance to provide students with a thorough understanding of real-world business. The fresh, contemporary text design features user-friendly tables, figures and diagrams that make theoretical explanations, such as the technical aspects of accounting transactions, more accessible. End-of-chapter assignments have also been enhanced, so that you now have a range of difficulty levels to choose from. This aids students with independent practice and learning at their own standard of ability.